Chemical reprogramming culture for the expansion of salivary gland epithelial basal progenitor cells - Ye Jin Jeong; Yongpyo Hong; Yeo-Jun Yoon; Nam Suk Sim; Seung-Min Hong; Jae-Yol Lim (Stem Cell Research & Therapy)
Abstract Background Salivary gland (SG) hypofunction presents a significant clinical challenge with limited treatment options. SG epithelial cells offer a promising approach due to their intrinsic tissue specificity and regenerative potential. However, the lack of efficient culture methods has hindered their clinical use. Methods This study presents a chemical reprogramming culture (CRC) system that utilizes a combination of three small molecules for the long-term two-dimensional culture of human SG epithelial progenitor cells. We characterized the cultured cells, measured their organoid-forming efficiencies, and assessed their differentiation potential. To evaluate the therapeutic efficacy of the SG basal progenitor cells (SG-BPCs), we administered them into a mouse model with radiation-induced SG hypofunction and assessed the functional recovery. Results By utilizing optimal concentrations of the small molecules Y-27632, A83-01, and LDN193189, the SG epithelial cells achieved over 50 population doubling levels (PD) within 80 d, surpassing the Hayflick limit. β-galactosidase and Terminal deoxynucleotidyl transferase dUTP nick end labeling staining confirmed that these small molecules inhibited cellular senescence and apoptosis, respectively. The cells expressed SG basal ductal cell markers KRT5, KRT19, and SOX9, with increased expression levels observed from PD5 to PD40. Notably, these expanded cells were able to differentiate into various SG cell types, including acinar and myoepithelial cells, indicating that SG-basal progenitor cells (SG-BPCs) were selectively proliferated using our CRC method. To assess the therapeutic potential of the expanded SG-BPCs, they were administered to mice with radiation-induced SG hypofunction. The treatment successfully restored SG function. Conclusion Our findings demonstrate that our CRC system is an effective method for the long-term culture of SG-BPCs. This advancement holds significant promise for the development of SG epithelial progenitor-based therapies to treat SG hypofunction.